2020
DOI: 10.47941/jep.373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formative Classroom Assessment in Saudi Arabian Elementary Schools

Abstract: Purpose: This study investigates the effect of formative classroom assessment (FCA) on elementary school pupils in Saudi Arabia.Methodology: The duration of the study covered one entire academic year. The work was based on an experimental design of two tests: pre- and post-test. The number of participants was 120 pupils of mixed gender. The participants were purposively sampled for this study. The study’s two tests were based on the Basic Science Achievement Test (BSAT). The pupil’s test feedback was validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Furthermore, the findings are consistent with those of Shah (2014), who found that the experimental group's mean performance scores on a post-test were considerably higher than the control group. This is not unexpected because, according to Alashwal (2020), formative assessment is beneficial to students because it assists in the diagnosis of learning challenges and the understanding of topic difficulties, allowing students to enhance their academic learning outcomes.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…Furthermore, the findings are consistent with those of Shah (2014), who found that the experimental group's mean performance scores on a post-test were considerably higher than the control group. This is not unexpected because, according to Alashwal (2020), formative assessment is beneficial to students because it assists in the diagnosis of learning challenges and the understanding of topic difficulties, allowing students to enhance their academic learning outcomes.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…Assessment involves multiple techniques in the form of written, oral and performance/demonstration formats in groups or individually. Assessment does not cover only the learning outcomes at the end of specific period of instruction but also the participation in learning by bringing classroom instruction and assessment together as learners are exposed to some contents (Orlando 2020). Assessment is designed to collect information about the quality of an individual's work or performance in terms of knowledge, skills, attitude or behaviour using a variety of procedures to collect the desired information (Johnson & Morris, 2009: Rabinowitz, 2010.…”
Section: Introductionmentioning
confidence: 99%